2009
DOI: 10.4161/cc.8.16.9354
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin-dependent kinase inhibitors, cki-1 and cki-2, act in overlapping but distinct pathways to control cell-cycle quiescence duringC. elegansdevelopment

Abstract: Cyclin-dependent kinase inhibitors (CKIs) are major contributors to the decision to enter or exit the cell cycle. The Caenorhabditis elegans genome encodes two CKIs belonging to the Cip/Kip family, cki-1 and cki-2. cki-1 has been shown to act as a canonical negative regulator of cell-cycle entry, while the role of cki-2 remains unclear. We identified cki-2 in a genome-wide RNAi screen to reveal genes essential for developmental cell-cycle quiescence. Examination of cki-2 knockout animals revealed extra rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…We found also that SAS-4 foci are rarely present in diakinesis GCs carrying the null allele cki-2(ok2105), and always disappear thereafter, suggesting that cki-2 contributes only in a minor fashion to timely elimination (Fig. 6D) (Buck et al, 2009).…”
Section: Centriole Elimination Is Delayed In Germ Cells Depleted Of Tmentioning
confidence: 73%
See 2 more Smart Citations
“…We found also that SAS-4 foci are rarely present in diakinesis GCs carrying the null allele cki-2(ok2105), and always disappear thereafter, suggesting that cki-2 contributes only in a minor fashion to timely elimination (Fig. 6D) (Buck et al, 2009).…”
Section: Centriole Elimination Is Delayed In Germ Cells Depleted Of Tmentioning
confidence: 73%
“…However, more recent findings using a cki-2 deletion allele instead led to the suggestion that CKI-2 is not needed for centriole elimination, raising the possibility that the earlier observation resulted from pleiotropic effects of cosuppression (Buck et al, 2009). Apart from the possible role of CKI-2 in this process, other components and mechanisms that contribute to elimination are not known.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This L1-L3 VPC quiescence is maintained with amazing precision in wild type animals, suggesting a robust system of redundant controls that are coupled to developmental signals. Genetic studies of mutants displaying precocious VPC cell cycle entry identified regulators of VPC quiescence [4][5][6][7][8][9][10] that include prB/CKi pathways at the interface of cell cycle and development the evolutionarily conserved retinoblastoma protein (pRB, the product of the lin-35 gene in C. elegans 10,11 ) and cyclin-kinase inhibitors (CKIs) of the Cip/Kip family (of which there are two family members in C. elegans, encoded by the cki-1 and cki-2 genes 5,6,[8][9][10] ). Recent work from the Saito lab, reported on page XXX of this issue of Cell Cycle, 5 adds new understanding of the complex functional relationships among pRB and CKI pathways that ensure the precise developmental control of VPC quiescence and cell cycle reentry.…”
mentioning
confidence: 99%
“…7 Moreover, since the screen demands that precocious VPC cell divisions produce cells with the lin-12-responsiveness of normal VPCs, purely cell cycle phenotypes can be distinguished from more general developmental timing defects characteristic of heterochronic genes. 4 Buck et al 5 identified cki-2 as a regulator of VPC quiescence, and placed cki-2 in a pathway regulating cyclin E (and hence likely as an inhibitor of CDK-2/ cyclin E 12 ). They then employed a series of genetic interaction experiments to characterize the functional relationships between cki-2 and its other family member, cki-1, and with the another key quiescence factor, pRB/LIN-35.…”
mentioning
confidence: 99%